PEMBUATAN LKS IPA BERORIENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) UNTUK MATERI ZAT ADIKTIF DAN PSIKOTROPIKA, BUNYI, CAHAYA DAN ALAT OPTIK DI KELAS VIII SMP/MTS - Syerly Kumala; Masril Masril; Harman Amir (Universitas Negeri Padang, 2016)
One of the problems encountered science subjects in school are the low yields obtained student learning. It is caused by many factors, one of which is the lack of learning tools to support the process of learning science. Therefore it is necessary to study the device is designed in the form of science worksheet. Given this research aims to produce products such as student activity sheet materials for teaching science to the subject matter of addictive and psychotropic substances, noise, light and optical equipment. This research is the development (research and development) of model Plomp. This model consists of five phases which initial investigation (preliminary investigation), the design phase (design), the phase of realization / construction (realization / construction), phase test, evaluation, and revision (test, evaluation and revision) and an implementation phase (implementation). However, this research is only done through 4 phases. To test the validity of science worksheet taken yan made the subject lecturer of physics as many as four people. While testing the practicalities of junior high science teacher made as many as 5 people. Data was analyzed with descriptive analysis technique. Based on research that has been done, the resulting product in the form of student activity sheet PBI models oriented science lessons. Products are categorized valid study of aspects of the worksheet completeness, appropriateness of content, language use student activity sheet, and kegrafisan student activity sheet with an average value of 86.25%. Product research is also considered practical by the teacher with the average value of 82.41% from the aspects of ease of use, time efficiency, and benefits